Effect of Chinese Personal Income Tax Adjustment on Income Distribution Based on General Equilibrium - Li, Baofeng; Guo, Huanhuan; Zang, Hongmin; Chen , Tigui (Transformations In Business & Economics, 2025)
Personal income tax is the most important tax type to regulate the distribution of residents’ income in China, but how the redistributive effect of personal income tax, the existing literature lacks an in-depth analysis based on general equilibrium. To explore the impact of personal income tax on resident income distribution, drawing on general equilibrium theory, a Computable General Equilibrium (CGE) model of taxation was constructed, the Social Accounting Matrices (SAM) based on the four issues of China’s Input-output Table published in the past decade were compiled, the effect of personal income tax on resident income distribution was comprehensively measured and vertically compared from income effect and consumption effect. Results show that: (1) levying personal income tax narrows the income gap among urban, rural, and national residents, indicating a progressive nature of taxation. Chinese personal income tax taxpayers are mainly concentrated in high-income groups, which is the main reason for the progressive nature of Personal income tax. (2) Across time, the redistributive effect of the personal income tax increased period by period before the 2018 tax reform, and then weakened after the tax change. The conclusions provide reference significance for further reforming China’s tax system and improving the income distribution pattern.